Competencies of the Special Education Student Teachers: A Systematic Review - Bazrafshan, Sabereh; Zaraii Zavaraki, Esmaeil; Sharifi Daramadi, Parviz; Delavar, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Special education of student teachers requires highly specialized competencies to get prepared to teach the students with special needs and to predict and cope with problems that may occur during their work. This study explored the definition and domains of special education student teachers competencies. This study was a systematic review of special education student teachers' competencies in English databases (2000-2020). A comprehensive search through multiple known databases identified a dataset of 112 papers, from which 23 papers were retrieved in the final step. Individual, social, ethical, methodological, and professional domains were defined as belonging to special education student teachers’ competence. Moreover, factors affecting the development of the competencies were identified. Although the competencies and their domains vary by culture and across countries, this systematic review demonstrated the comprehensive ones in these scopes.